KESALAHAN STRUKTUR SINTAKSIS PADA SKRIPSI MAHASISWA JURUSAN BAHASA DAN SASTRA ARAB UIN BANDUNG TAHUN 2014 (KAJIAN SINTAKSIS ARAB) - Hilya Sakinah Najah; Faiz Abdul Aziz Al Hakim; Rohanda Rohanda (Jurnal Bastra (Bahasa dan Sastra), 2026)
This study aims to analyze structural errors in Arabic found in undergraduate theses written by students of the Arabic Language and Literature Department at UIN Sunan Gunung Djati Bandung in 2014. The study was motivated by the continued presence of various grammatical mistakes in Arabic sentence writing, which should adhere to the rules of nahwu and sharaf (Arabic linguistics). The research was conducted using a descriptive qualitative method. Ten theses were collected through documentation techniques and analyzed to identify the types of errors and their underlying causes. The findings showed that the most frequent errors involved the incorrect use of i‘rab, mismatches between masculine and feminine forms, inconsistencies in idhafah and na‘t–man‘ut constructions, errors in noun usage, and mismatches between ‘adad (number) and ma‘dud (counted noun). The main factors contributing to these errors were the students’ limited mastery of Arabic grammar and interference from their first language. These findings highlight the importance of strengthening the teaching of nahwu and sharaf in academic writing, as this may help students minimize grammatical errors in future research.